0
Demostrar que si :

Abierto 1 Respuestas 11 Vistas

 B\subseteq A ,\, entonces \, A-\left ( A-B \right )=B.

1 Respuesta

0

A-(A-B)=A\, \cap \, \left ( A\, \cap \, B^{c} \right )^{c} \\ =A\, \cap \, \left ( A^{c}\, \cap \, \left ( B^{c} \right )^{c} \right ) \\ = A\, \cap \, \left ( A^{c}\, \cup \, B \right )\\ =\left ( A\, \cup \, A^{c} \right )\cup \left ( A\, \cap B \right )\\ = \o\, \cup \, \left ( A\, \cap \, B \right )= A\cap B

Como \, B\subseteq A,   entonces A\cap B= A  y  A\cap B= B.

Por lo tanto, 

B\subseteq A \Rightarrow A-\left (A-B \right )=B.

respondido por anónimo Ago 21, 2017
...